“JUGAE” Project: Together winning in efficiency (Journal of Parents and Teachers, 2013)
The author presents a projects that emerges from the necessity of collaboration between family and school in the educative ambit. It was developed in a school in Jerez de la Frontera and its main objective is to help the students in the process of making decisions. It is based on the systemic approach and designed for working with behaviors and relationships in a periods of time that last around 2 years.
Keywords: Family; decisions; behaviors; interpersonal relationships; experience